Lower Bounds for the Partial Grundy Number of the Lexicographic Product of Graphs - Domingues, Kenny; Oliveira, Yuri Silva de; Silva, Ana (Anais do Encontro de Teoria da Computação (ETC), 2021)
A Grundy coloring of a graph $G$ is a coloring obtained by applying the greedy algorithm according to some order of the vertices of $G$. The Grundy number of $G$ is then the largest $k$ such that $G$ has a greedy coloring with $k$ colors. A partial Grundy coloring is a coloring where each color class contains at least one greedily colored vertex, and the partial Grundy number of $G$ is the largest $k$ for which $G$ has a partial greedy coloring. In this article, we give some results on the partial Grundy number of the lexicographic product of graphs, drawing a parallel with known results for the Grundy number.